Diagnostic value of ultrasound-guided needle biopsy in undiagnosed pleural effusions: A systematic review and meta-analysis. Issue 27 (2nd July 2020) - Lin, Zhidi; Wu, Donghong; Wang, Jinlin; Wang, Chuqiao; Huang, Mingkai
Abstract: Background and Objective: Undiagnosed pleural effusions (UPEs) are a common problem of respiratory medicine, leading to an increased diagnostic burden globally. However, the most efficient and cost-effective approaches to UPEs remain controversial. This study aimed to assess the diagnostic value of ultrasound-guided needle biopsy (UGNB) in UPEs. Methods: We conducted a search of PubMed, Embase, the Cochrane Library and reference lists of retrieved studies with no publication data limitation. Articles that investigated the diagnostic accuracy of UGNB in UPEs were included. The quality of eligible studies was assessed using Quality Assessment of Diagnostic Accuracy Studies-2. The diagnostic value of UGNB was evaluated by calculating the pooled sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, diagnostic odds rate, and the area under the curve for the summary receiver operating characteristic curve using a random effects model. Results: Seven studies comprising 165 patients with UPEs met the inclusion criteria. UGNB had a pooled sensitivity of 83% (95% confidence intervals [CI], 75% - 89%), a specificity of 100% (95% CI, 90% - 100%), a positive likelihood ratio of 8.89 (95% CI, 3.29 - 24.02), a negative likelihood ratio of 0.23 (95% CI, 0.16 - 0.33), a diagnostic odds rate of 51.47 (95% CI, 14.70 - 180.16), and an area under the curve of 0.94. Six pneumothorax cases (3.6%), 5 local wound infections (3.0%), and 1 empyema case (less than 1%) were observed. There was no significant heterogeneity or publication bias in this study. Conclusions: Based on current evidence, UGNB is a safe and convenient procedure with a high accuracy for diagnosing UPEs. However, physicians should still be cautious in interpreting negative UGNB results.